Gender – Fair Language in Teaching Basic Education: Basis for Capability Building - Gamboa, Jerame N.; Bacani, Michael Angelo; Baluyut, Jennifer; Galura, Olive N.; Manalastas, Kristine E. (Future Science / FSH-PH Publications, 2022)
Education aims to create equality and respect through its components. One of those components is the learning delivery of any subject matter wherein language is mainly utilized. The study aimed to determine the usage of the gender sensitive language in teaching basic education at Don Honorio Ventura State University. It specifically sought to answer on the level of familiarity of the teachers on the gender-fair language; the frequency on the teacher’s usage of the gender-fair language; the common gender-fair terminologies used in motivation, discussion, performance tasks, assessments, and assignments; and the difficulties that the teachers encountered in using gender-fair language. The study used sequential explanatory type of research. It used questionnaires and interviews in gathering data. There are 65 participants who answered the survey and 11 of them participated in the focal group discussion. Based on the findings, the teachers are familiar with the gender-fair language but they sometimes use them in various areas of teaching such as in motivation, discussion, performance task, assessment, and assignment due to the topic pertinence and student ability. With those findings, the conduct of wide dissemination through capability building on the use of gender-fair language is still needed.